The Effect of Drug Inventory Management on the Accuracy of Prescription Services in Pharmaceutical Installations - Marbun, Romauli Anna (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The accuracy of prescription services is a key indicator of hospital pharmacy service quality. One of the factors influencing service timeliness is effective drug inventory management. Objective: This study aimed to analyze the effect of drug inventory management on the accuracy of prescription services at the Pharmacy Installation of Grandmed Lubuk Pakam Hospital. Research Methods: This research employed a quantitative approach with a descriptive-analytic design. Samples were randomly selected prescriptions served. Data were collected through direct observation, interviews, and document analysis, and analyzed using simple linear regression. Results: The average prescription service time for non-compounded drugs was 40 minutes and 75 minutes for compounded drugs, exceeding the standards set by the Ministry of Health. Regression analysis showed that drug inventory management significantly influenced prescription service timeliness, with a regression coefficient of 0.45 (p=0.002). Conclusion: Optimal drug inventory management contributes to the acceleration of prescription service time. It is recommended that the hospital improve the stock monitoring system, optimize procurement processes, and strengthen interdepartmental coordination to support pharmacy service efficiency.